Overview of Adolescent Diet and Nutritional Status During The Covid-19 Pandemic at SMAN 17 Surabaya - Novita Machfiratul Jannah; Taufiqurrahman; Juliana Christyaningsih; Dian Shofiya (Journal of Nutrition Explorations, 2025)
Adolescents are prone to nutritional problems due to unhealthy eating habits, worsened by lifestyle changes during the COVID-19 pandemic. This study aimed to describe the eating patterns and nutritional status of adolescents at SMAN 17 Surabaya. A descriptive quantitative design was used, involving 38 randomly selected Grade XI students from November 2021 to March 2022. Data were collected through anthropometric measurements and a validated Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), then analyzed descriptively. The majority of respondents were 17 years old (63.2%) and female (73.7%). While all respondents were categorized as having good food types based on diversity, most exhibited severe macronutrient deficits, most had severe deficits in energy (73.7%), protein (42.1%), fat (52.6%), and carbohydrates (84.2%). Consumption of vegetables, fruits, and protein sources was low. All respondents (100%) had poor dietary patterns. Nutritional status showed that 68.4% were normal, 13.2% underweight, 10.5% overweight, and 7.9% obese. Schools, parents, and health professionals are encouraged to improve adolescents' nutrition through education, monitoring, and promoting balanced diets with adequate intake of fruits, vegetables, and protein.